Immunogenicity of Augmented Compared With Standard Dose Hepatitis B Vaccine in Pediatric Patients on Dialysis: a Midwest Pediatric Nephrology Consortium Study - Misurac, Jason M. (Clin J Am Soc Nephrol, 2017)
BACKGROUND AND OBJECTIVES: Patients on maintenance dialysis have a higher risk of unresponsiveness to hepatitis B vaccination and loss of hepatitis B immunity. Adult guidelines recommend augmented dosing (40 mcg/dose), resulting in improved response in adults. We sought to determine whether children on dialysis mount a similar antibody response when given standard or augmented dosing of hepatitis B vaccine. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: This is a retrospective review of patients on dialysis aged <19 years from May 1, 2008 to May 1, 2013 at 12 pediatric dialysis units. Hepatitis B surface antibody (HBsAb) titers ≥10 mIU/ml were defined as protective. RESULTS: A total of 187 out of 417 patients received one or more hepatitis B vaccine boosters. The median age was 13 years; the cohort was 57% boys and 59% white. Booster dose or HBsAb titers were missing in 17 patients. Conversion to protective HBsAb titers was achieved in 135 out of 170 patients (79%) after their first single-dose booster or multidose booster series. In patients receiving a single-dose booster, the response rate was 53% (nine out of 17) after a 10 mcg dose, 86% (65 out of 76) after a 20 mcg dose, and 65% (17 out of 26) after a 40 mcg hepatitis B vaccine dose. In patients receiving a multidose booster series, the response rate was 95% (19 out of 20) after a 10 mcg/dose series, 83% (20 out of 24) after a 20 mcg/dose series, and 71% (five out of seven) after a 40 mcg/dose series. Patients receiving a multidose booster series had a response rate of 86% (44 out of 51), compared with 76% (91 out of 119) in patients receiving a single-dose booster (P=0.21). Twenty-seven patients received more than one single-dose booster or multidose series, and 26 out of 27 (96%) eventually gained immunity after receiving one to three additional single-dose boosters or multidose booster series. CONCLUSIONS: There was no clear gradient of increasing seroconversion rate with increasing vaccine dose in this cohort of pediatric patients on dialysis.